How Graphic Organizer Model Effects on Learners Writing Ability - Friendis Syani Amrulloh (JEET, Journal of English Education and Technology, 2022)
This research aims to know how Graphic Organizer Model Effects on Learners Writing Abilities which population of this research was the students of first-grade Mts. Mambaus Sholihin, there were 38 students. In this research, researchers used simple random sampling. The research method was a Pre-Experimental design conducted in one group pre-test and post-test. To analyze the data, the researcher used paired sample t-tests to determine whether there was a significant effect before and after treatment in the Experimental class. The Implication of this research is the Graphic Organizer Method's effectiveness in the students' descriptive writing in first grade in MTs. Mambaus Sholihin. The Originality of this research is that researchers used the Graphic Organizer method for practical Descriptive writing Students. The result showed that the experimental group scores significantly differed before or after being taught the Graphic organizer method. Based on the results of the pre-test and post-test with the comparison of the magnitude of t that we get in the manual counting (t0) = 12,59 and the magnitude of t listed in the table of values (t.ts.5% = 2.03), we can know that t0 is more significant than tt .2.03 > 12,59. So it can be concluded that the hypothesis is accepted or Ha is accepted, while Ho is rejected.